2020
DOI: 10.1007/s42452-020-1938-6
|View full text |Cite
|
Sign up to set email alerts
|

On the estimation of the friction factor: a review of recent approaches

Abstract: The friction factor is traditionally computed through Colebrook's equation or by using Moody's chart. However, these approaches have shown their limitations in getting accurate values for such factor. Different models to calculate the friction factor have been proposed, achieving different levels of certainty. In this paper, we revisit the distinct strategies used to estimate the friction factor and propose the use of a modified version of a model proposed by these authors. This model is based on the phenomeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…Further, for example, US Bureau of Mines published a report in 1956 [10] that introduced a modified form of the Colebrook equation for gas flow where coefficient 2.51 was replaced with 2.825. Also, very recent modifications of a variety of empirical equations for pipe flow are available [11]. Here we analyze one modification for air flow friction in the open-cathode side of the observed type of PEMFCs [8], and subsequently, we give a stable and computationally efficient explicit solution which is valid in this case.…”
Section: Modified Colebrook Equation For Flow Frictionmentioning
confidence: 99%
“…Further, for example, US Bureau of Mines published a report in 1956 [10] that introduced a modified form of the Colebrook equation for gas flow where coefficient 2.51 was replaced with 2.825. Also, very recent modifications of a variety of empirical equations for pipe flow are available [11]. Here we analyze one modification for air flow friction in the open-cathode side of the observed type of PEMFCs [8], and subsequently, we give a stable and computationally efficient explicit solution which is valid in this case.…”
Section: Modified Colebrook Equation For Flow Frictionmentioning
confidence: 99%
“…Re Re Re H . (10) In this study, the Reynolds number was substituted with a generalized Re number due to Madlener et al [12] in Eq. ( 3).…”
Section: Friction Factor Formulationsmentioning
confidence: 99%
“…Brkič [8] and Genić et al [9] presented extensive reviews of the existing approaches and found many explicit approximations very accurate. Plascencia et al [10] also compared current methods; they discovered that some expressions using Lambert's W function are also sufficiently precise. Some recent, unified formulations are valid for all hydraulic regimes for Newtonian fluids [11].…”
Section: Introductionmentioning
confidence: 99%
“…The main strength of the model from [28,29] is in assuming the sharp flow transition as a sigmoid type of function that results from the randomness of the flow associated with the turbulence; 2.…”
Section: Background and Related Workmentioning
confidence: 99%